2018
DOI: 10.1037/rmh0000091
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among Latina farmworkers and other employed Latinas in North Carolina.

Abstract: The mental health of Latinas with manual occupations, particularly those employed in agriculture, is a public health concern. The goals of this analysis were to describe the mental health of Latina farmworkers, and to compare their mental health with that of other Latina manual workers. Participants included 35 employed Latina farmworkers, 35 employed non-farmworkers, and 25 unemployed non-farmworkers who completed interviews in 2012. Measures included stress, anxiety, depressive symptoms, elevated depressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 53 publications
4
33
1
1
Order By: Relevance
“…Consistent with these findings, previous research has found Latina farmworkers to experience greater stress and anxiety than Latinas who were employed in other occupations [ 30 ]. Further, employed Latinas (both farmworkers and non-farmworkers) were found to experience greater stress and anxiety than unemployed Latinas [ 30 ].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Consistent with these findings, previous research has found Latina farmworkers to experience greater stress and anxiety than Latinas who were employed in other occupations [ 30 ]. Further, employed Latinas (both farmworkers and non-farmworkers) were found to experience greater stress and anxiety than unemployed Latinas [ 30 ].…”
Section: Discussionsupporting
confidence: 82%
“…Six of the pesticide biomarkers we measured met our criteria for quality assurance and frequency of detection: malathion dicarboxylic acid (MDA), para-nitrophenol (PNP), 3,5,6-tricholor-2-pyridinol (TCPY), 3-phenoxybenzoic acid (3-PBA), the trans isomer of 3-(2,2-dichlorovinyl)-2-2-dimethylcyclopropane carboxylic acid (trans-DCCA), and 2,4-dichlorophenoxyacetic acid (2,4-D). Five of these, MDA, PNP, TCPY, 3-PBA and trans-DCCA, represent exposure to organophosphate and pyrethroid insecticides, which have been associated with neurological dysfunction in agricultural workers [ 30 ]. The metabolite 2,4-D represents exposure to an herbicide that has been associated with cancer in agricultural workers [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher mental disorder levels and poorer vitality have been reported for animal farmers [90,91] and dairy farmers [90,92], compared to non-farmers. Others also find a higher prevalence of mental disorders in farm workers as compared to employed non-farmworkers and other occupations such as teaching, office work, and building construction [62,86,90,93,94,95,96,97,98,99,100,101]. Wheeler et al [26] identified that some Australian irrigators experienced high levels of psychological distress nationally; higher than dryland farmers or the Australian population.…”
Section: Systematic Review Resultsmentioning
confidence: 99%
“…2,3 Many also experience chronic diseases, including diabetes, tuberculosis, and hypertension, [4][5][6][7][8] as well as significant mental health problems, including stress, depression, and alcohol use disorders. [9][10][11][12] However, these farmworkers have limited access to conventional health services. 13,14 Mexicans and Mexican Americans access a wide array of traditional healers and other complementary therapies.…”
Section: Introductionmentioning
confidence: 99%